Biosurfactant production of entomopathogenic Bacillus subtilis BK7.1, as potential biocontrol bacteria, isolated from Baluran National Park, East Java, Indonesia - SALAMUN SALAMUN; RIZKY DANANG SUSETYO; NI’MATUZAHROH NI’MATUZAHROH; FATIMAH FATIMAH; ALMANDO GERALDI; AGUS SUPRIYANTO; TRI NURHARIYATI; FARAH AISYAH NAFIDIASTRI; NABILATUN NISA’; ENDARTO ENDARTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Salamun, Susetyo RD, Ni’matuzahroh, Fatimah, Geraldi A, Supriyanto A, Nurhariyati T, Nafidiastri FA, Nisa’ N, Endarto. 2023. Biosurfactant production of entomopathogenic Bacillus subtilis BK7.1, as potential biocontrol bacteria, isolated from Baluran National Park, East Java, Indonesia. Biodiversitas 24: 1785-1792. Biosurfactants as biocontrol agents have received much attention for pest control and disease vectors. The research aimed to identify the species and genetic relationship, hemolytic activity, detect coding genes, and trial production of biosurfactants on various substrates of entomopathogenic Bacillus sp. BK7.1 isolated from natural soil in Baluran National Park, East Java, Indonesia. Biosurfactant screening was carried out by testing hemolytic activity, surface tension, and emulsification activities, detecting coding genes of biosurfactant biosynthesis, and testing biosurfactant production in various substrates. The results of the molecular identification by amplifying the 16S rRNA gene using the Polymerase Chain Reaction (PCR) method for Bacillus sp. BK7.1 has a genetic similarity of 98.68% with B. subtilis subsp. inaquosorum strain BGSC 3A28. Screening showed positive hemolytic activity results, reduced surface tension, increased emulsification activities, and the production of biosurfactant in glucose, glycerol, and molasses substrates. The PCR results showed that Bacillus sp. BK7.1 had srfAA and srfAD genes encoding surfactin biosynthesis, giving it the potential to produce bioinsecticide compounds. Based on these studies, the indigenous entomopathogenic B. subtilis BK7.1 can be developed as environmentally friendly microbial bioinsecticides for pest control and disease vectors.